Effect of mix design methods on the mechanical properties of steel fibre-reinforced concrete prepared with recycled aggregates from precast waste. (October 2020) - Anike, Emmanuel Ejiofor; Saidani, Messaoud; Olubanwo, Adegoke Omotayo; Tyrer, Mark; Ganjian, Eshmaiel
Highlights: The use of different mix design methods attracts different optimum steel fibre content. Equivalent Mortar Volume (EMV) mix proportioning technique can be applied to steel fibre-reinforced recycled concrete. The EMV mix design method is more cost-effective than its conventional counterpart. The EMV guide requires over 68% more superplasticizer compared to the traditional method. The presence of SF increases pore density thereby affecting the durability of the concrete. Abstract: This research investigates the impact of mix design methods on the mechanical characteristics of steel fibre-reinforced concrete (SFRC) made with recycled aggregates (RA) obtained from a precast waste concrete. The experimental campaign was carried out in two phases. In phase I, three types of steel fibre (SF) differing only in shape were examined. Then, eight mixes were formulated, considering a range of SF volume ratios from 0.125% to 1.5%, using both normal and the Equivalent mortar volume (EMV) mix design methods. In phase II, a reference mix and two recycled aggregate concrete mixes were developed, one designed with normal method and the other with the EMV technique and incorporating their associated optimum SF content obtained in phase I. The results show that the mechanical properties of SFRC proportioned with the EMV approach is not adversely affected and that water absorption capacity of the concrete is improved with this method compared to the traditional method. Also, mix design method adopted for recycled concrete affects the optimum SF volume ratio.